S49 Increased skeletal muscle-specific microRNA-1 in the blood of COPD patients. (2nd December 2011) - Donaldson, A V J; Lewis, A; Natanek, A; Man, W D; Kemp, P; Polkey, M I
Abstract : Introduction: Quadriceps muscle dysfunction is an important prognostic comorbidity in COPD. MicroRNAs (miRs) are small non-coding RNAs that regulate gene expression. Skeletal muscle expresses a number of tissue-specific microRNA including miR-1, which modulates muscle phenotype. MicroRNAs can be secreted from cells and maintained in blood within exosomes. Elevated levels of circulating miR-1 have been demonstrated in a number of human and animal models of muscle disease. We hypothesised that plasma levels of miR-1 would be elevated in COPD patients and would correlate with important physiological parameters. Methods: 103 COPD patients and 25 controls were studied. MiR-1 was quantified in stored plasma samples using q-RT PCR.1 MiR-16 and miR-122 were quantified as negative controls. Results were normalised to an exogenous spiked-in control. Results: Characteristics as mean (SD); COPD patients: M: 67, F: 36, age=66.47 (8.4), FEV1 % pred= 43.5 (18.6), 6-minute walk (6MW) = 394 (120). Controls: M: 14, F: 11, age=67 (8.1), FEV1 % pred=111.2 (13.1), 6MW=613 (83). Plasma miR-1 was significantly elevated in COPD patients, p=0.002. There was no difference in miR-16 and miR-122. MiR-1 was negatively associated with FEV1 % predicted (r =−0.3, p<0.001) and with Tlco (r=−0.3, p<0.001), but it was not possible to distinguish between GOLD stages using ANOVA. However, if patients were sub-divided into early GOLD stage COPD (1 and 2) or late GOLD stage COPD (3 and 4), miR-1 was significantly higher in the latter group (p=0.02). The plasma level of miR-1 was inversely correlated with daily activity measured as locomotion time (r= −0.25, p<0.01) but miR-1 levels were not associated with any muscle phenotype or with muscle-specific gene expression. Conclusion: Our results show that stable COPD patients have elevated plasma levels of muscle-specific miR-1. The increase in miR-1 may be due to increased muscle degradation or turnover in the COPD patients studied. Our work raises the possibility of using other muscle-specific microRNAs in the future as potential biomarkers of muscle dysfunction in patients with COPD.